Ethnomathematics Walewangko House in Project-Based Learning to Enhancing Students’ Creative Thinking and Mathematical Disposition - Ngala, Januarius Clief; Marsigit, Marsigit (Jurnal Kependidikan: Jurnal Hasil Penelitian dan Kajian Kepustakaan di Bidang Pendidikan, Pengajaran dan Pembelajaran, 2024)
This research aims to examine the effectiveness of Project-based Learning (PjBL) method based on ethnomathematics of Walewangko house on students' creative thinking skills and mathematical disposition. This study employed a quantitative approach with a quasi-experimental design. The sample consists of one experimental class with 34 eighth-grade students. The research instruments included pretests and posttests on creative thinking skills as well as a mathematical disposition questionnaire, both of which have been validated for reliability and validity. Data analysis comprised descriptive and inferential statistical analyses. The inferential statistical methods used were paired sample t-tests and one-sample t-tests. The results of this study indicated that: (1) there is an improvement in students' creative thinking skills and mathematical disposition before and after the learning method was applied, (2)  the posttest results for creative thinking skills and mathematical disposition meet the respective standard scores, (3) the percentage of classical completeness in the posttest results for both creative thinking skills and mathematical disposition exceeds 85%. It can be concluded that the Project-Based Learning method based on the ethnomathematics of Walewangko house is effective in improving students' creative thinking skills and mathematical disposition. Integration of ethnomathematics as a basis for learning, in addition to acting as a contextual learning innovation, teachers are also expected to introduce and instill in students cultural values related to the ethnomathematics used.